Pengaruh Pemasaran Media Sosial dan Hubungan Pelanggan pada Loyalitas Merek dengan Keterlibatan Pelanggan Sebagai Variabel Intervening - Celia Adinda Wibowo; Patria Laksamana (J-MAS (Jurnal Manajemen dan Sains), 2023)
The aim of this study is to determine the influence of Social Media Marketing and Customer Relations on Brand Loyalty with Customer Engagement as a mediating variable, a case study on Shopee Indonesia in 2022 using the Technology Acceptance Model (TAM) theory and Theory of Reasoned Action (TRA) in collaboration with the variables above. This study used an analytical tool, namely SEM-PLS and was conducted on 200 Generation Z respondents. The results of Social Media Marketing research mediated by Customer Engagement, do not affect Brand Loyalty simultaneously. Likewise Customer Relationship mediated by Customer Engagement, do not affect Brand Loyalty simultaneously. Although there have been many studies related to the object of research on E-commerce Shopee, this research measures brand loyalty as influenced by Social Media Marketing and Customer Relations mediated by Customer Engagement. Focusing on Brand Loyalty using the Shopee application by involving Generation Z respondents.